2016
DOI: 10.1177/2150135116634290
|View full text |Cite
|
Sign up to set email alerts
|

Giant Right Atrial Aneurysm: Antenatal Diagnosis and Surgical Treatment

Abstract: Giant congenital right atrial aneurysms are rare, with their natural history complicated by death, heart failure, arrhythmias, and thrombosis. Prenatal diagnosis of the defect is feasible and allows an early preparation of a plan for management. We present details of a patient diagnosed prenatally with a giant right atrial aneurysm, which was successfully treated surgically as soon as the patient became symptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Some researchers believe IERA as a benign condition not affecting life expectancy [7, 35], but others suggested its complications were life-threatening, including refractory arrhythmias, RHF, thromboembolic events, and sudden death [6, 34, 36]. This review found 4 sudden cardiac deaths due to refractory atrial tachycardia or RHF in 153 IERA patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers believe IERA as a benign condition not affecting life expectancy [7, 35], but others suggested its complications were life-threatening, including refractory arrhythmias, RHF, thromboembolic events, and sudden death [6, 34, 36]. This review found 4 sudden cardiac deaths due to refractory atrial tachycardia or RHF in 153 IERA patients.…”
Section: Discussionmentioning
confidence: 99%
“…For asymptomatic patients, some clinicians suggested prophylactic resection to avert possible complications [4, 26, 43, 44]. Others, however, suggested a watchful waiting in combination with regular follow-up [6]. Some patients responded well to the surgical treatment while others were more responsive to the nonsurgical approach [3, 10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In general, the risk of operative mortality is low but not zero, and is higher for the youngest patients. 2,10 This age effect is seen in pediatric heart surgery in general, even in operations of relatively low complexity. Caution has been urged against RAA resection without cardiopulmonary bypass 6,10,11 and against rushing into elective open-heart surgery before three years of age.…”
Section: Discussionmentioning
confidence: 99%
“…But monitoring with serial ECG, Holter, and echocardiograms will identify events, which are usually not life-threatening in asymptomatic patients and amenable to medical therapy and RAA resection. 10…”
Section: Discussionmentioning
confidence: 99%